Role of cultivation intensity in shaping the net carbon footprint of Mediterranean cow-calf systems - Lunesu, Mondina Francesca; Caratzu, Maria Francesca; Sechi, Sara; Pulina, Giuseppe; Battacone, Gianni; Nudda, Anna (Frontiers in Animal Science, 2026)
This study aimed to estimate the net carbon footprint (Net CFP) of Mediterranean cow–calf systems and to assess the role of cultivation intensity in shaping environmental performance. Eighteen beef farms adopting a cow–calf grazing system with an open productive cycle were considered. Farms were selected according to cultivation rate (CR) and classified as high (high-CR; >15% of cultivated land) or low (low-CR;<15% of cultivated land). Data were collected through farmer interviews using a cradle-to-farm-gate approach, in accordance with ISO 14040:2006 and ISO 14044:2006 standards. The average of five production years was used as the temporal boundary. Emission intensity was expressed as kilograms of CO2 equivalent (CO2e) per kilogram of live weight (LW) sold from yearling beef, per kilogram of total LW sold from end-career cows, bulls, and yearling beef, and per hectare of land. Soil carbon sequestration was estimated by accounting for above- and belowground biomass residues and organic carbon from manure deposition. Carbon sequestration from Meriagos, forests, and Mediterranean scrubland was also included. Gross CFP was lower in low-CR farms than in high-CR farms (19.80 vs. 26.75 kg CO2e/kg LW sold). Enteric methane was the main contributor, accounting for 68.3% and 74.2% of total greenhouse gas emissions in high- and low-CR farms, respectively. When carbon sequestration was included, Net CFP was significantly lower (P<0.01) in low-CR farms. In conclusion, lower cultivation intensity reduced the CFP of cow–calf systems by generating higher carbon credits that could fully offset emissions from the fattening phase. However, this potential is based on farm-level estimates and does not automatically translate into certified carbon credits. Therefore, further work is needed to assess eligibility and practical implementation within formal carbon crediting frameworks.